Effectiveness of nurse led screening and intervention for common non communicable diseases in a peri urban community of Chandigarh - Paul, Damini; Kavita, Kavita; Thakur, Jarnail Singh; Sikka, Pooja (International Journal Of Community Medicine And Public Health, 2020)
Background: Globally the non-communicable diseases (NCDs) are accountable for most of mortality and disability. The Lack of skilled human resources for health is one of the contributing factors for low screening coverage. Nurses plays a vital role, in the early detection and prevention of common NCDs. Objective of the study was to assess the effectiveness of nurse-led screening and intervention for common NCDs on risk factor modifications. Methods: Pre-experimental design was used in the present study. The study was done in slum area Indra colony Chandigarh. A total of 500 individuals aged ≥30 years were enrolled from 2,700 households. All the subjects were screened for hypertension, diabetes mellitus and oral cancer. However in female participants addition screening of breast, and cervical cancer was also done. WHO STEPS survey was used to assess the risk factor of common NCDs. The interventional package on risk factor modifications for prevention of common NCDs was developed and was delivered to all subjects during home visits. The follow up to assess risk factor modifications was done after one month. The primary outcome of the study was risk factor modifications and prevalence of common NCDs. Results: There was significant mean change in systolic blood pressure (0.65±6.31 mmHg), diastolic blood pressure (1.19±3.7 mmHg), body mass index (0.95±0.85 kg/m2), and waist circumference (1.5±1.46 cm) among subjects after one month of intervention (p value <0.05). Conclusions: The Nurse-led screening and intervention for common NCDs was effective in risk factor modification among studied subjects.